2019
DOI: 10.1021/acs.iecr.9b00616
|View full text |Cite
|
Sign up to set email alerts
|

Copper Foam Electrodes for Increased Power Generation in Thermally Regenerative Ammonia-Based Batteries for Low-Grade Waste Heat Recovery

Abstract: The use of porous copper foam to increase the electrode surface area and power generation in thermally regenerative ammonia-based batteries (TRABs) is proposed and investigated. The incorporation of copper foam leads to a 38% increase in maximum power compared to that of typical copper plate. The electrode thickness not only influences the electrode surface area but also affects mass transfer, especially the ammonia transfer inside the anode. The optimal thickness of copper foam in terms of total charge, power… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…Previous reports have only considered two cell designs for assessing the performance of a TRAB: (i) a closed batch system (Figure S1a) that embodies a traditional electrochemical H-cell configuration and (ii) an electrodialysis type setup that has a spacer gasket between the electrodes and membranes for the liquid solutions to flow through . Until now, a zero gap design for the TRAB with flow of the anolyte and catholyte has not been considered despite its ubiquitous use in redox flow batteries (RFB). ,, There is significant merit for the zero gap flow design for a TRAB (which is termed here as the ammonia flow battery (AFB)) because this battery has a 0.4 V open-circuit voltage (OCV), and thus, any sources of resistance can quickly diminish the power output from the battery when extracting electrical current. A zero gap design entails direct contact of the Cu mesh electrodes with an AEM separator.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports have only considered two cell designs for assessing the performance of a TRAB: (i) a closed batch system (Figure S1a) that embodies a traditional electrochemical H-cell configuration and (ii) an electrodialysis type setup that has a spacer gasket between the electrodes and membranes for the liquid solutions to flow through . Until now, a zero gap design for the TRAB with flow of the anolyte and catholyte has not been considered despite its ubiquitous use in redox flow batteries (RFB). ,, There is significant merit for the zero gap flow design for a TRAB (which is termed here as the ammonia flow battery (AFB)) because this battery has a 0.4 V open-circuit voltage (OCV), and thus, any sources of resistance can quickly diminish the power output from the battery when extracting electrical current. A zero gap design entails direct contact of the Cu mesh electrodes with an AEM separator.…”
Section: Introductionmentioning
confidence: 99%
“…14 Until now, a zero gap design for the TRAB with flow of the anolyte and catholyte has not been considered despite its ubiquitous use in redox flow batteries (RFB). [7][8][9][10][11][12]14,15 There is significant merit for the zero gap flow design for a TRAB (which is termed here as the ammonia flow battery (AFB)) because this battery has a 0.4 V open-circuit voltage (OCV), and thus, any sources of resistance can quickly diminish the power output from the battery when extracting electrical current. A zero gap design entails direct contact of the Cu mesh electrodes with an AEM separator.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Low-grade waste heat (temperature <130 °C) generated from industrial and geothermal processes is a large energy resource that may be utilized through energy recovery. Among various recovery methods, one promising technology is the conversion of low-grade waste heat into electricity using solid-state thermoelectric system based on semiconductor materials (STES), , organic Rankine cycle (ORC), , and membrane-based thermo-osmotic systems (MTOS). , However, expensive material and/or operational costs, poor energy storage capacity, and relatively complex system of STES and ORC limit their development. , MTOS technologies have resulted in low power densities and energy efficiencies, although these technologies are scalable and less expensive. , To convert low-grade heat to electricity, it is necessary to develop a new technology that is less expensive, scalable, and is easy to put into production. , …”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, it was shown that the relatively small specific surface area of two-dimensional electrodes significantly limited TRAB performance . To increase the electrode surface area and improve the maximum performance of TRAB, the use of three-dimensional (3D) copper foam was proposed . However, on the one hand, the uneven distribution of ammonia resulted in a high local concentration of ammonia and fast anodic reaction on the part of the copper foam in the anode.…”
Section: Introductionmentioning
confidence: 99%
“…Carbon paper and carbon felt electrodes are examples of 3-D, open-cell, fluid-permeable electrodes that have been used instead of traditional 2-D electrodes in applications such as redox flow batteries, water purification, , and electrocatalytic conversions . Copper and nickel metallic foams or felts have also been used in electrocatalytic conversions (e.g., electrolytic water splitting), , thermal regenerating ammonia batteries, glucose sensing, , and electrocatalytic organic reactions . To the best of our knowledge, 3-D, open-cell, noble-metal electrodes are not currently used as electrodes in electroanalysis or electrocatalysis, despite the fact that 2-D noble-metal electrodes (e.g., wires, rods, foils, or disks) have found several applications in electroanalysis (detection of heavy metals, pesticides, , DNA , ), electrocatalytic conversions (electroreduction of CO 2 ), water oxidation, fuel cells, , and flow batteries .…”
Section: Introductionmentioning
confidence: 99%